KELAYAKAN FLASH CARD SUBMATERI MANFAAT KEANEKARAGAMAN HAYATI KELAS X SMA KABUPATEN LANDAK - Hartati, Angel Tri; Syamswisna, Syamswisna; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis study aims to find out the feasibility of flash cards media in the benefits of biodiversity sub material for Senior High School tenth in Landak Regency. The method used in this study was qualitative research using the descriptive. Validation sheet was used as the instrument of research. Each statement item is divided into categories Very Good is worth 4, Good is worth 3, Less Good is worth 2, and Not Good is worth 1. Since the data is in qualitative form, then to calculate it needs to be converted into a quantitative form using the Lawshe formula. Validation results from the validator can be analyzed using Content Validity Ratio (CVR) analysis. The flashcards feasibility as a learning media was then being verified by two lecturers of Biology major in Faculty of Teachers Training and Education Tanjungpura University and three Biology teachers for Senior High School tenth grader from three high schools in Landak Regency. Based on the verifier assessments, the flashcards are valid with the total average validation value 0.99 and feasible to be used as learning media in the benefits of biodiversity sub material. Keywords: Biodiversity, flash cards, Kabupaten Landak